A Population-Based Assessment of Awareness and Understanding of Clubfoot in the Aseer Region, Saudi Arabia - Alqahtani, Turki Ahmed; Riazah, Abdulla Fahad; Althwabi, Mohammed Yahya; Alshabab, Mohanad Qasem; Alnakhli, Ghadeer Redha; Abdulrahman, Majdoleen Ali; Alasmari, Faris Mohammed; Alqahtani, Saud Abdullah; Alnuwayhidh, Ali Mushabib; Faya, Hamad Khalid (Journal of Neonatal Surgery, 2025)
Background: When recognized early, clubfoot is a treatable condition. The lack of public awareness about clubfoot, however, can cause treatment to be delayed. The purpose of this study was to evaluate public awareness about clubfoot in the Aseer region, Saudi Arabia. Methods: We performed a cross-sectional survey that included Saudi Arabian residents of the Aseer regions from July to December 2022. An online survey was devised by orthopedic experts to gather information on public knowledge of clubfoot risk factors, treatment options, surgical complications, and prognosis. Regardless of whether they were familiar with someone who had clubfoot, the target sample consisted of 476 individuals from all age groups and both sexes in the general population. Results: A total of 476 participants completed the online survey; 58.6% were male and their ages ranged from 18 years to more than 50 years. A total of 245 (51.5%) have never heard about club foot. The analysis showed 365 (76.7%) of our participants had a poor level of awareness about clubfoot (Achieving less than 60% on the awareness questionnaire). The most common source of awareness about clubfoot was relatives and friends (26.1%), followed by social media (22.1%), websites (12.6%), and books and magazines (10.9%) whereas 43.9% did not have a source of their information about clubfoot. Citing books and magazines as the source of information about clubfoot was associated with good awareness level (X2 = 43.800, p < .01). Conclusion: The study found that the majority of people in the Aseer region were unaware of clubfoot. It was found that up to 76.7% of people had a low level of awareness about the illness. The only important variable linked to good clubfoot awareness was the source of knowledge.